A longitudinal evaluation of improvements in radiotherapy treatment plan quality for head and neck cancer patients. Issue 2 (May 2016) - Tol, Jim P.; Doornaert, Patricia; Witte, Birgit I.; Dahele, Max; Slotman, Ben J.; Verbakel, Wilko F.A.R.
Abstract: Purpose: To investigate changes in head-and-neck cancer (HNC) plan quality following the introduction of new technologies and planning techniques in the last decade. Methods and materials: Thirty plans were selected from each of four successive periods (P). P1: 7-field static intensity-modulated radiotherapy (IMRT) with parotid gland sparing; P2: dual-arc volumetric-modulated arc therapy (VMAT, similar to P3-P4), including submandibular gland sparing; P3: inclusion of individual swallowing muscles and attempts to further reduce parotid and oral cavity doses through manual interactive optimization; P4: containing the same organs-at-risk (OARs) as P3, but automatically interactively optimized. Plan benchmarking included mean salivary gland/swallowing muscle/oral cavity (Dsal /Dswal /Doc ) doses. Differences in mean doses between the periods were analyzed by an ANCOVA, taking geometric differences across periods into account. Results: Compared to P1, P2 plans improved Dsal by 3.4 Gy on average. P3 improved Dsal /Dswal /Doc by 6.9/11.5/7.2 Gy over P2, showing that Dswal and Dsal could be improved simultaneously. In P4, Doc /Dswal slightly improved over P3 by 1.7/3.8 Gy. Improved OAR sparing in P3/P4 did not come at the cost of increased dose deposition elsewhere and planning target volume (PTV) dose homogeneity was similar. Conclusions: New technologies and planning techniques were successfully implemented into routine clinical care and resulting in improved HNC plan quality.